2022
DOI: 10.1101/2022.09.09.22279426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 and CoronaVac against pediatric COVID-19-associated hospitalization and moderate-to-severe disease

Abstract: Background: Vaccine effectiveness (VE) of BNT162b2 and CoronaVac against COVID-19-associated hospitalization and moderate-to-severe disease due to SARS-CoV-2 Omicron BA.2 for pediatric populations that had low exposure to prior SARS-CoV-2 variants needs to be further clarified. This can be studied from the 1.36 million vaccine doses had been administered to 766,601 of 953,400 children and adolescents in Hong Kong (HK) since March 2021 to April 2022. Methods: Using an ecological design leveraging the HK vaccin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the effect estimates underlying the calculated vaccine effectiveness varied across studies. Although vaccine efficacy from RCTs 24 , 25 was based on incidence rate ratios, considering person-years to address surveillance time, vaccine effectiveness from NRSIs was calculated on the basis of incidence rate ratios, 29 , 30 , 40 , 42 , 49 , 50 hazard ratios, 43 , 44 , 47 RRs, 45 or ORs. 27 , 28 , 32 , 46 , 48 , 51 , 52 , 53 , 54 However, no outliers were identified in meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT and 24 observational studies were included. Seventeen studies were excluded for incorrect population or intervention [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and 10 were excluded based on being ongoing trials. PLOS GLOBAL PUBLIC HEALTH will be monitored for publication as well as studies under consideration for inclusion.…”
Section: Search Resultsmentioning
confidence: 99%
“…1 The premarketing phase 3 clinical trial with 2 doses of the pediatric BNT162b2 mRNA vaccine administered 3 weeks apart and conducted before the emergence of Omicron showed an efficacy of 90.7% (95% CI, 67.7-98.3). 2 Initial postmarketing studies evaluating vaccine effectiveness (VE) in children 5-11 years old showed reduced estimates during the Omicron era [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and suggested rapid waning by 1-4 months after the last vaccine dose. 5,8,10,[12][13][14][15]17,18 Few studies reported VE against specific Omicron subvariants in children 8,11,16,17 or investigated whether VE may be modified with longer interval between doses, 13 as reported in adolescents 19 and adults.…”
mentioning
confidence: 99%
“…2 Initial postmarketing studies evaluating vaccine effectiveness (VE) in children 5-11 years old showed reduced estimates during the Omicron era [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and suggested rapid waning by 1-4 months after the last vaccine dose. 5,8,10,[12][13][14][15]17,18 Few studies reported VE against specific Omicron subvariants in children 8,11,16,17 or investigated whether VE may be modified with longer interval between doses, 13 as reported in adolescents 19 and adults. 20 In Canada, the recommended interval between doses was 8 weeks in contrast to the 3-week interval recommended by the manufacturer.…”
mentioning
confidence: 99%